2013
DOI: 10.1152/physrev.00008.2012
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptors in Bone Physiology and Diseases

Abstract: During the last decade, our view on the skeleton as a mere solid physical support structure has been transformed, as bone emerged as a dynamic, constantly remodeling tissue with systemic regulatory functions including those of an endocrine organ. Reflecting this remarkable functional complexity, distinct classes of humoral and intracellular regulatory factors have been shown to control vital processes in the bone. Among these regulators, nuclear receptors (NRs) play fundamental roles in bone development, growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 570 publications
0
41
0
2
Order By: Relevance
“…Although estrogens are recognized predominantly for their function in female mammalian reproduction and the development of secondary sex characteristics, namely uterine and mammary effects, they also play important roles in almost every physiologic system of the body (Edwards, 2005) in both women and men (Lombardi et al, 2001;Finkelstein et al, 2013). As pharmaceutical targets, estrogens and their varied antagonists have been particularly important in contraception (Benagiano et al, 2006) and breast cancer therapy (Jensen and Jordan, 2003), with an increasing appreciation of their therapeutic value in the nervous (McEwen et al, 2012), immune (Cunningham and Gilkeson, 2011), vascular (Knowlton and Lee, 2012), skeletal (Imai et al, 2013), and endocrine systems . For decades, the actions of estrogen(s) were thought to be mediated by a single estrogen receptor first identified in the 1960s (Jensen and Jacobson, 1962;Jensen and DeSombre, 1973), that is, until the discovery of a second highly homologous estrogen receptor in 1996 (Kuiper et al, 1996), whereupon the first estrogen receptor was renamed estrogen receptor a (ERa) and the new receptor ERb.…”
Section: Introductionmentioning
confidence: 99%
“…Although estrogens are recognized predominantly for their function in female mammalian reproduction and the development of secondary sex characteristics, namely uterine and mammary effects, they also play important roles in almost every physiologic system of the body (Edwards, 2005) in both women and men (Lombardi et al, 2001;Finkelstein et al, 2013). As pharmaceutical targets, estrogens and their varied antagonists have been particularly important in contraception (Benagiano et al, 2006) and breast cancer therapy (Jensen and Jordan, 2003), with an increasing appreciation of their therapeutic value in the nervous (McEwen et al, 2012), immune (Cunningham and Gilkeson, 2011), vascular (Knowlton and Lee, 2012), skeletal (Imai et al, 2013), and endocrine systems . For decades, the actions of estrogen(s) were thought to be mediated by a single estrogen receptor first identified in the 1960s (Jensen and Jacobson, 1962;Jensen and DeSombre, 1973), that is, until the discovery of a second highly homologous estrogen receptor in 1996 (Kuiper et al, 1996), whereupon the first estrogen receptor was renamed estrogen receptor a (ERa) and the new receptor ERb.…”
Section: Introductionmentioning
confidence: 99%
“…It has become clear that controlling the expression level, subcellular distribution, and even the subnuclear distribution of TFs are all key regulatory mechanisms to control gene expression. 17,18 Traditional biochemical methods for understanding each of these mechanisms are often time-consuming, fail to capture the cellular heterogeneity in a population, and are not easily amendable to high-throughput screening.…”
Section: Mia: Tf Assaymentioning
confidence: 99%
“…As mentioned earlier, AGD and perineum muscle formation are also effective indicators of masculinization. The musculoskeletal system is sensitive to the action of androgen as documented in the effect of synthetic androgens on bone density and muscle mass [Imai et al, 2013]. It has been suggested that AR is present within the muscles and is involved in postnatal growth of BC/ LA muscles through AR-positive satellite cells [Chen et al, 2005].…”
Section: Hormonal Control Of the Sexually Dimorphic External Genitaliamentioning
confidence: 99%